Respuesta :

  x = -22/3 = -7.333


Step by step solution : Step  1  :Equation at the end of step  1  : x 1 (—-(—•(12-x)))-((7x+3•(8-x))-8) = 0 2 2 Step  2  : 1 Simplify — 2 Equation at the end of step  2  : x 1 (— - (— • (12 - x))) - (4x + 16) = 0 2 2 Step  3  :Equation at the end of step  3  : x (12 - x) (— - ————————) - (4x + 16) = 0 2 2 Step  4  : x Simplify — 2 Equation at the end of step  4  : x (12 - x) (— - ————————) - (4x + 16) = 0 2 2 Step  5  :Adding fractions which have a common denominator :

 5.1       Adding fractions which have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

x - ((12-x)) 2x - 12 ———————————— = ——————— 2 2 Equation at the end of step  5  : (2x - 12) ————————— - (4x + 16) = 0 2

x=18 hope this helps